UHMWPE biomaterials handbook ultra high molecular weight polyethylene in total joint replacement and medical devices - Kurtz, Steven M., 1968- (Academic, 2009)
This book describes the science, development, properties and application of of ultra-high molecular weight polyethylene (UHMWPE) used in artificial joints. This material is currently used in 1.4 million patients around the world every year for use in the hip, knee, upper extremities, and spine. Since the publication of the 1st edition there have been major advances in the development and clinical adoption of highly crosslinked UHMWPE for hip and knee replacement. There has also been a major international effort to introduce Vitamin E stabilized UHMWPE for patients. The accumulated knowledge on these two classes of materials are a key feature of the 2nd edition, along with an additional 19 additional chapters providing coverage of the key engineering aspects (biomechanical and materials science) and clinical/biological performance of UHMWPE, providing a more complete reference for industrial and academic materials specialists, and for surgeons and clinicians who require an understanding of the biomaterials properties of UHMWPE to work successfully on patient applications.
Previous edition: published as The UHMWPE handbook. 2004.
Keywords: Artificial joints.; Ultrahigh molecular weight polyethylene.; Plastics in medicine.; elektronické knihy; electronic books